InCl3-Catalyzed [2+3] Cycloaddition Reaction: A Rapid Synthesis of 5-Substituted 1H-tetrazole under Microwave Irradiation - Vijay S. Patil; Kamlakar P. Nandre; Amulrao U. Borse; Sidhanath V. Bhosale (E-Journal of Chemistry)
A series of 5-substituted 1H-tetrazole were efficiently prepared by InCl3 catalyzed (10 mol %) from structurally divert organic nitriles with sodium azide under the influence of microwave irradiation. The present protocol was successfully applied to the aliphatic, aryl, benzylic and heterocyclic nitriles and corresponding 5-substituted 1H-tetrazole were obtained in good to excellent yield (70-96%). This method gives remarkable advantages such as short reaction time, simple work-up procedure and economical beneficial.